Understanding multivariate research : a primer for beginning social scientists - Berry, William Dale (Westview Press, 2000)
Gives new social science graduate students sufficient background in quantitative multivariate analysis (e.g., regression analysis) to allow them to read research relying on such analysis prior to formal training in statistical methods.